2018
DOI: 10.1096/fj.201801429rr
|View full text |Cite
|
Sign up to set email alerts
|

Stress hormone signaling through β‐adrenergic receptors regulates macrophage mechanotype and function

Abstract: Critical functions of immune cells require them to rapidly change their shape and generate forces in response to cues from their surrounding environment. However, little is known about how soluble factors that may be present in the microenvironment modulate key aspects of cellular mechanobiology—such as immune cell deformability and force generation—to impact functions such as phagocytosis and migration. Here we show that signaling by soluble stress hormones through β‐adrenoceptors (β‐AR) reduces the deformabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 82 publications
0
22
0
Order By: Relevance
“…For example, stress hormones — epinephrine and norepinephrine — govern fight-or-flight responses by modulating muscle contraction [ 14 ]. Stress hormone activation of the β -adrenergic receptor ( β -AR) signaling pathway further impacts macrophage mechanobiology, decreasing the deformability of macrophage cells through the rearrangement of branched filamentous actin in the cortical region [ 15 ]. Such a decrease in cell deformability induced by β -AR activation is also associated with an increase in macrophage phagocytosis and chemotaxis [ 15 ].…”
Section: Mechano-regulation Of Innate Immunitymentioning
confidence: 99%
See 1 more Smart Citation
“…For example, stress hormones — epinephrine and norepinephrine — govern fight-or-flight responses by modulating muscle contraction [ 14 ]. Stress hormone activation of the β -adrenergic receptor ( β -AR) signaling pathway further impacts macrophage mechanobiology, decreasing the deformability of macrophage cells through the rearrangement of branched filamentous actin in the cortical region [ 15 ]. Such a decrease in cell deformability induced by β -AR activation is also associated with an increase in macrophage phagocytosis and chemotaxis [ 15 ].…”
Section: Mechano-regulation Of Innate Immunitymentioning
confidence: 99%
“…Stress hormone activation of the β -adrenergic receptor ( β -AR) signaling pathway further impacts macrophage mechanobiology, decreasing the deformability of macrophage cells through the rearrangement of branched filamentous actin in the cortical region [ 15 ]. Such a decrease in cell deformability induced by β -AR activation is also associated with an increase in macrophage phagocytosis and chemotaxis [ 15 ]. Moreover, environmental pathogens can change host cell mechanotypes.…”
Section: Mechano-regulation Of Innate Immunitymentioning
confidence: 99%
“…Further, cardiac macrophages are responsible for impaired myocardial relaxation and aggravated myocardial stiffness while diastolic dysfunction develops (Hulsmans et al, 2018). It is known that β-ARs are expressed on the surface of macrophages in most tissues, and macrophage mechanotype and function can be regulated through β-AR by stress hormone signal (Kim et al, 2019). In this study, the data demonstrated that STAT6 deficiency promotes macrophage differentiation from CD11b + IMCs and recruits them into the injured hearts after chronic stimulation of β-AR, which in turn aggravated cardiac fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…In that sense its effect on the morphological and functional activity of the macrophages merits attention. It has been reported that epinephrine regulates the size, morphology, motility and the capacity for phagocytosis of rat peritoneal macrophages and modulates their immune responses by affecting their capability for cytokine production [6][7][8]. Notably, the kind of cytokines produced by immune cells is related to the type of receptors activated by catecholamines.…”
Section: Effect Of Epinephrine On Cell Proliferationmentioning
confidence: 99%
“…Notably, the kind of cytokines produced by immune cells is related to the type of receptors activated by catecholamines. Stimulation of α-adrenoreceptors induces TNFα and IL-1β production, while incitement of β-adrenoreceptors results in inhibition of TNFα, IL-1β, IL-2, IL-4, IL-6, IL-10 and IL-12 secretion [7,9,10]. It has been shown that stimulation of α2-adrenoreceptor expressed on lamina propria mononuclear cells accelerated the progress of experimental colitis in mice, while their blockade restrained the inflammatory response and ameliorated the progress of the disease [11].…”
Section: Effect Of Epinephrine On Cell Proliferationmentioning
confidence: 99%